Hematological Abnormalities in Hepatitis A Viral Infection in Children - Alia Afzal, Javed Tahir, Aimen Javed, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hepatitis A virus (HAV) infection remains a significant cause of pediatric morbidity in endemic regions. While the disease is typically self-limiting, extrahepatic manifestations, including hematological changes, have important clinical implications. Objective: This cross-sectional study aimed to determine the frequency and pattern of hematological alterations among children with acute HAV infection. Methods: A total of 160 children aged 1–15 years with serologically confirmed HAV (anti-HAV IgM positive) were recruited from the Department of Pediatrics, Jinnah Hospital, Lahore. Complete blood counts, prothrombin time (PT), activated partial thromboplastin time (APTT), and liver function tests were performed. Results: Results showed that 63.8% of children exhibited hematological abnormalities, while 36.2% maintained normal profiles. The most prevalent abnormalities were leukocytosis (20%), anemia (16.3%), and thrombocytosis (11.3%), followed by leukopenia (8.1%) and thrombocytopenia (8.1%). Stratified analysis revealed significant associations between hematological abnormalities and demographic variables. Male children demonstrated higher frequencies of leukocytosis and thrombocytopenia (p<0.001), while leukopenia was restricted to older children (9–15 years, p<0.001). Thrombocytopenia was significantly more frequent in younger children (1–8 years, p=0.005). Additionally, leukopenia and thrombocytopenia were more common among children with normal BMI compared to overweight/obese peers (p<0.001 and p=0.005, respectively). Conclusion: No mortality occurred in the study cohort, and most hematological disturbances were transient and self-limiting. These findings emphasize that hematological manifestations are common in pediatric HAV and may complicate disease presentation. Recognition of such abnormalities is crucial for early management, particularly in endemic and resource-limited settings. Further multicenter studies are warranted to explore their prognostic relevance and underlying mechanisms. Keywords: Hepatitis A virus, children, hematological abnormalities, leukocytosis, thrombocytopenia